Molecular and Histochemical Analysis of Jatropha Curcas Linn. Transgenic Using Tolerance Antibiotics Hygromycin (hpt) and β-Glucuronidase (gus-A) Gene. (2015) - Maftuchah,; Zainudin, Agus; Pahlevi, Robby Wahyu; Anggriawan, Arik
Abstract: To improve Jatropha curcas's trait, genetic engineering technology genetic engineering development is needed. This study was aimed to analyze transgenic of J. curcas with plasmid vectors pCambia-1304. The study was conducted using primer hpt (forward) 5'-GATGCCTCCGCTCGAAGTAGCG-3', (reverse) 5'-GCATCTCCCGCCGTGCAC-3', gus-A (forward) 5'–GCCATTTGAAGCCGATGTCACGCC-3' and (reverse) 5'-GTATCGGTGTGAGCGTCGCAGAAC-3'. The PCR results elucidated five plants (16.67%) positive hpt gene, 22 plants (77.33%) positive gus -A gene. Histochemical test results showed 16 plants (53.33%) positive hpt test. A total of 24 plants (80%) resulted positive gus -A gene on leaf and 11 plants (36.67%) resulted positive gus -A gene on the root.